Four-top as probe of light top-philic New Physics - Alvarez, Ezequiel (2019)
We study the four-top (tt¯ tt¯) final state at the LHC as a probe for New Physics (NP) effects due to new particles that couple predominantly to the top quark and whose masses are below the top-quark-pair production threshold. We consider simple NP models containing a new particle with either spin 0, spin 1, or spin 2, and find benchmark points compatible with current experimental results. We find that interference effects between NP and QED amplitudes can be large, pointing out the necessity of NLO contributions to be explicitly computed and taken into account when NP is present. We examine kinematic differences between these models and the Standard Model (SM) at the parton level and the reconstructed level. In the latter case, we focus on events selected requiring two same-sign leptons and multiple jets. We investigate how the different Lorentz structure of the light NP affects the kinematic hardness, the polarization, the spin correlations, and the angular distributions of the parton-level and/or final-state particles. We find that spin-2 light NP would be identified by harder kinematics than the SM. We also show that the angular sepa- ration between the same-sign leptons is a sensitive observable for spin-0 NP. The spin-0 and spin-2 NP cases would also yield a signal in tt¯ γγ with the invariant mass of the photons in- dicating the mass of the new particle. The spin-1 NP would be identified through an excess in four-top signal and slight or not modification in other observables, as for instance the lack of signal in tt¯ γγ due to the Landau-Yang theorem. We comment on the opportunities that would open from the kinematic reconstruction of some of the top quarks in the tt¯ tt¯ state. Our results provide new handles to probe for light top-philic NP as part of the ongoing experimental program of searches for four-top production at the LHC Run 2 and beyond.